Effect of varying nitrogen levels on growth, development and yield of winter barley (Hordeum vulgare L.) in semi-arid region of Southern Afghanistan - Abdul Wahed Kohistani; Anil K. Choudhary (Annals of Agricultural Research, 2023)
A field experiment was conducted at Experimental Farm of Afghanistan National Agricultural Sciences and Technology University (ANASTU), Kandahar, Afghanistan during winter season of 2014-15 to assess the optimum nitrogen (N) dose for barley besides assessing the effect of varying N levels (0, 40, 60, 80, 100, 120, 140 kg N ha–1) on growth, development and yield of winter barley under semi-arid conditions of Afghanistan in a randomized block design replicated thrice in a sandyclay loam soil. The results revealed that increase in N levels from 0 to 140 kg N ha–1 led to consistent and significant increase in growth parameters and biological yield of barley; however, yield attributes viz. number of effective tillers, number of grains/spike, grains weight/spike, 1000-grains weight as well as grain yield (3.5 t ha–1) were significantly highest when we applied N @ 120 kg ha–1. The biological yield was significantly highest when N was applied @ 140 kg N ha–1. In nutshell, application of N @ 120 kg N ha–1 may enhance the growth, development and grain yield of winter barley (Hordeum vulgare L.) in semi-arid region of Afghanistan.